Employee Performance Based on Contribution of WFH, Organizational Commitment, and Organizational Culture at Bagian Umum Sekretariat Daerah Pemerintah Kota Kupang - Jefirstson Richset Riwukore; Juhaini Alie; Sandys Vena Ade Putri Hattu (UNIVED Press, 2022)
The purpose of this research is to analyze and prove the effect of WFH, organizational commitment, and organizational culture on employee performance. This research was conducted for 5 months (January-May 2022) at the General Secretariat of the Kupang City Government. This research is classified as a quantitative study using a confirmative verification (associative) survey method. The research population was 105 employees whose sample was determined based on the census technique (saturated sample) so the sample was 105 respondents. The type of research data consists of primary data and secondary data. Techniques to obtain data using questionnaires (Likert scale), interviews, and documentation. Data analysis used multiple linear regression analysis (partial test and simultaneous test). The results showed that the variables of WFH, organizational commitment, and organizational culture had a positive and significant effect on employee performance either partially or simultaneously. This is because the entire t-count value obtained by each variable is greater than the t-table and also the F-count is greater than the F-table with a significance value less than 0.05. The results of this study also show the contribution of the WFH variable to employee performance by 67.9%, organizational commitment to employee performance by 55.8%, and organizational culture to employee performance by 49%. Simultaneously, the contribution of WFH, organizational commitment, and organizational culture to employee performance is 74%. Based on the results of this study, the biggest contribution to employee performance is the implementation of the WFH policy, followed by organizational commitment, and organizational culture.